Privatization in Africa - White, Campbell Oliver; Bhatia, Anita; International bank for reconstruction and development / world bank (Washington, DC : World Bank, 1998)
The study had three key components: the construction of a database of privatization transactions in frica, a set of ten country case studies, and an analysis of the role and extent of world Bank and donor assistance in support of privatization. In the course of the study, we reviewed the avalaible literature on privatization in Africa, both to draw on additional information and to compare our findings.
Includes bibliographical references (p. 157-159)
aia 16/08/16
Loans
Keywords: Privatization; Africa, Sub-Saharan